Longitudinal associations between informal caring, social network, and psychological distress among adolescents and young adults: modelling within-person effects - Miharu Nakanishi; Satoshi Yamaguchi; Mai Sakai; Hatsumi Yoshii; Syudo Yamasaki; Atsushi Nishida; Takahiro Tabuchi (BMC Public Health)
Abstract Background Informal caring is associated with mental health deterioration among young people and impacts their help-seeking ability. Social network can provide social support and mitigate the impact of informal care. However, young carers may avoid identification and withdraw from social networks. Evidence regarding the reciprocal associations between caring, social network, and mental health is scarce. We aimed to investigate the directionality and specificity of the associations among the three factors in young people. Methods This study used three consecutive assessment data (2021–2023; T0–T2) from the Japan COVID-19 and Society Internet Survey. We included 5539 young persons aged ≤ 25 years and 25,445 adults aged 26–59 years. Social network was measured using the Lubben Social Network Scale. Psychological distress was evaluated using the Kessler Psychological Distress Scale. Caring status was retrospectively reported at T2. We employed a random intercept cross-lagged model to detect within-person prospective associations between informal caring, social network, and psychological distress. Results Young persons showed significant directional relationships from increased social network and psychological distress at T0 to increased likelihood of caring at T1 (standardised coefficient: 0.131 and 0.176, respectively; 95% confidence interval, 0.015–0.247 and 0.071–0.282, respectively). Adults aged 26–59 years showed a reverse relationship from caring to increased psychological distress both from T0 to T1 (0.061, 0.009–0.112) and from T1 to T2 (0.042, 0.000–0.084). Conclusions Increased psychological distress and social network preceded the onset of informal caring among young persons. Incorporating psychological distress assessment may benefit the early identification of and support for young carers. The long-term interplay between social networking and informal caring needs further clarification.